Keynote speaker at "CE and SCP for the sustainable construction materials" at the 16th Asia Pacific Roundtable on Sustainable Consumption and Production (16th APRSCP 2022: Carbon Neutral Event) - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Sr Dr Asmah Alia Mohamad Bohari has been invited as keynote speaker at the 16th APSCP conference to discuss how far we have progressed regarding Sustainable Consumption and Production (SCP) up-scaling, in particular e-market for the green product in Malaysia. The event was held at Pathumwan Princess Hotel, Bangkok, Thailand on 21-23 November 2022. The conference was organized by the APSCP and The Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH (Thailand). The back-to-back roundtable discussion with the experts and practitioners from Thailand and beyond has been conducted for over 3 hours. The session was moderated by Kai Hoffman & Mrs Pimpilas from GIZ Germany alongside two other keynote speakers Mr Tobias Schleicher from Oeko Institute Germany & Assoc Prof Dr Natasha Khalil from Universiti Teknologi MARA Cawangan Perak. The session was attended by various government and private company representatives from Asia Pacific, namely Japan, Thailand, India, Indonesia, Vietnam and Singapore.